Qualified Advocacy for JustPeace: The Popes' World Day of Peace Messages (1968–2020) in Historical and Ethical Perspective. (21st June 2020) - Power, Maria; Hrynkow, Christopher
Abstract : During the past half century, the Catholic popes have promulgated World Day of Peace Messages. This article takes those messages as a corpus and critically examines them for their content that supports or detracts from a JustPeace ethic. The authors define JustPeace as combining two elements, peace and social justice, in a creative and mutually enhancing tension. The present article surveys three recurring themes that are particularly relevant to supporting a JustPeace ethic, namely the value of strong global systems and governance, ecological health, and the embrace of cultures of encounter and dialogue. Through these means, the authors demonstrate streams of support for a JustPeace ethic in Catholic Social Teaching while illustrating that such support is not provided without qualification by the popes. The article concludes that such an essential recovery is not a subservient or fundamentalist appropriation of either the ethical content of papal teaching or of the past, but the bringing forward of important concepts, in locally sensitive and meaningful ways, that have the potential to help establish a vital future.